2023
DOI: 10.1108/lhs-08-2022-0090
|View full text |Cite
|
Sign up to set email alerts
|

Turkish nurses' leadership orientations and clinical decision-making skills

Abstract: Purpose The purpose of this study was to determine the relationship between the leadership orientations of nurses and their clinical decision-making skills. Design/methodology/approach This descriptive study was conducted between June and December 2018 on nurses working at three hospitals in Turkey. This study was completed with 1,100 nurses. The Personal Information Form, Leadership Orientation Scale and Clinical Decision-Making Scale in Nursing were used for data collection. Findings A significant correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…This nding demonstrated that transformational leadership style was the only signi cant predictor of nurses' autonomy, with other variables like age, gender, education level, years of experience, and different leadership styles excluded as they did not signi cantly affect nurses' autonomy. Contrary to the previous statement, a study found signi cant correlations between the leadership orientations of nurses and various factors such as age, sex, employing institution, years of experience, managerial position, and satisfaction with the current unit of employment (p < 0.05) [25]. They also discovered a signi cant correlation between nurses' clinical decision-making skills and age, sex, and occupational status (p < 0.05).…”
Section: Discussioncontrasting
confidence: 58%
“…This nding demonstrated that transformational leadership style was the only signi cant predictor of nurses' autonomy, with other variables like age, gender, education level, years of experience, and different leadership styles excluded as they did not signi cantly affect nurses' autonomy. Contrary to the previous statement, a study found signi cant correlations between the leadership orientations of nurses and various factors such as age, sex, employing institution, years of experience, managerial position, and satisfaction with the current unit of employment (p < 0.05) [25]. They also discovered a signi cant correlation between nurses' clinical decision-making skills and age, sex, and occupational status (p < 0.05).…”
Section: Discussioncontrasting
confidence: 58%